PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PROFITABILITAS PERBANKAN SYARIAH DAN KONVENSIONAL DI INDONESIA PERIODE JUNI 2010–2013 - Gunartin . (Jurnal Akuntansi Aktual, 2015)
This study aimsto analyze (1) profitability, internal factors (CAR and NPL), and externalfactors (inflation and BI Rate) of islamic and conventionalbanking, (2) the influence ofinternal andexternal factors on the profitability of islamic and conventional banking, (3) differences inprofitabilityof conventional and islamic banking in Indonesia for the period June 2010–June 2013. For its sam-pling in this study used purposive sampling obtained nine islamic banks and nine conventional banks.The data of this study used secondary data from the website of each bank and also Bank Indonesia. Themethod of data analysis which was used is multiple linear regression analysis and compare meanindependent sampel test. The result analysis showed that the average profitability of islamic bankingand fluctuating higher than average profitability of conventional banking trends both are rising elas-tically. Average CAR of higher islamic banking and conventional banking volatile compared with adownward trend. The conventional banking trending rose nearly stagnant. Islamic banking NPL risingtrend fluctuated with elastically. The conventional banking NPL fluctuate with the downtrend in elatis.Inflation is relatively volatile with very elastic approaching downtrend stagnant. BI Rate relativelyvolatile with elastic downtrend. Internal factors (CAR and NPL) have a significant effect on profitabil-ity. While external factors (inflation and BI Rate) had no significant effect on the profitability of islamicand conventional banking. So, there are significant differences in the profitability of islamic and con-ventional banking in Indonesia period June 2010–June 2013.Keywords:internal factors, external factors, profitability, islamic banking, conventional banking